2006
DOI: 10.1016/j.str.2005.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Forkhead Domain of FOXP2 Bound to DNA

Abstract: FOXP (FOXP1-4) is a newly defined subfamily of the forkhead box (FOX) transcription factors. A mutation in the FOXP2 forkhead domain cosegregates with a severe speech disorder, whereas several mutations in the FOXP3 forkhead domain are linked to the IPEX syndrome in human and a similar autoimmune phenotype in mice. Here we report a 1.9 A crystal structure of the forkhead domain of human FOXP2 bound to DNA. This structure allows us to revise the previously proposed DNA recognition mechanism and provide a unifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
257
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(271 citation statements)
references
References 41 publications
(64 reference statements)
11
257
0
Order By: Relevance
“…Our computer search based on a motif scan identified both cdc2 and cdk5 kinases as candidates under very strict conditions (http:͞͞scansite.mit.edu). It has been also very recently suggested that FOXP dimers can bind cognate DNA sites separated far from each other or located on different DNA strands, possibly suggesting that the function of FOXP3 proteins for certain genes (e.g., cytokines affected in our study) highly depends on promoting the assembly of higher-order protein-DNA complexes with varying degrees (23).…”
Section: Discussionmentioning
confidence: 54%
“…Our computer search based on a motif scan identified both cdc2 and cdk5 kinases as candidates under very strict conditions (http:͞͞scansite.mit.edu). It has been also very recently suggested that FOXP dimers can bind cognate DNA sites separated far from each other or located on different DNA strands, possibly suggesting that the function of FOXP3 proteins for certain genes (e.g., cytokines affected in our study) highly depends on promoting the assembly of higher-order protein-DNA complexes with varying degrees (23).…”
Section: Discussionmentioning
confidence: 54%
“…S1B). Most notably we found that in the positions that have been identified as essential for domain-swap dimerization (11,12), the Fkh1/2 residues are similar or identical to those of the FoxP subfamily and not to those of the classical monomeric Fox proteins from mammals or yeast (Fig. 1A and Fig.…”
Section: Significancementioning
confidence: 93%
“…10). Whereas most forkhead domains bind DNA as monomers, crystallographic and biochemical studies of members of the human FoxP family have revealed that the forkhead domains of FoxP2 and FoxP3 form homodimers, in vitro and likely in vivo, through an exchange of corresponding domains (or subdomains) between monomers, referred to as domain-swapped dimers (11)(12)(13). Because Fkh1 and/or Fkh2 (Fkh1/2) have been shown to regulate origin firing through binding in cis to origins, Fkh1/2 dimerization would potentially provide a mechanism for clustering two or more Fkh1/2-bound origins in trans (14).…”
mentioning
confidence: 99%
“…The first site is located at the N terminus, the second one in the forkhead domain and the last one between NLS and NES (Figures 1 and 2). The second AKT/PKB phosphorylation site is located in the wing W2 of FOXO DBD close to the cluster of basic residues that are known to participate in DNA binding (Figures 3c and 6) Jin and Liao, 1999;Stroud et al, 2006;Tsai et al, 2006Tsai et al, , 2007. It has therefore been suggested that phosphorylation in this basic region might inhibit FOXO binding to DNA (Zhang et al, 2002).…”
Section: Phosphorylation Of the Foxo Dbdmentioning
confidence: 98%
“…Cluster of basic residues following helix H4 in the C terminus of FOXK1a DBD interacts with nucleotides upstream from the core sequence through hydrogen bonds and bridging water molecules. In the periphery of Jin and Liao, 1999;Stroud et al, 2006;Tsai et al, 2006Tsai et al, , 2007; gray, residues of FOXO4 that were predicted to be involved in DNA binding based on homology modeling (Boura et al, 2007); brown, AKT/protein kinase B (PKB)/serum-and glucocorticoid-inducible kinase (SGK) phosphorylation sites; red, non-AKT/PKB phosphorylation sites; and green, acetylation sites. Symbol (*) means that the residues in that column are identical in all sequences in the alignment.…”
Section: Structure Of Forkhead Dna-binding Domainmentioning
confidence: 99%